Chronic kidney disease (CKD) treatment burden among low-income primary care patients. (September 2015) - Kahn, Linda S; Vest, Bonnie M; Madurai, Nethra; Singh, Ranjit; York, Trevor RM; Cipparone, Charlotte W; Reilly, Sarah; Malik, Khalid S; Fox, Chester H
Objective: This study explored the self-management strategies and treatment burden experienced by low-income US primary care patients with chronic kidney disease. Methods: Semi-structured interviews were conducted with 34 patients from two primary care practices on Buffalo's East Side, a low-income community. Qualitative analysis was undertaken using an inductive thematic content analysis approach. We applied normalization process theory (NPT) to the concept of treatment burden to interpret and categorize our findings. Results: The sample was predominantly African-American (79%) and female (59%). Most patients (79%) had a diagnosis of stage 3 CKD. Four major themes were identified corresponding to NPT and treatment burden: (1) coherence—making sense of CKD; (2) cognitive participation—enlisting support and organizing personal resources; (3) collective action—self-management work; and (4) reflexive monitoring—further refining chronic illness self-care in the context of CKD. For each component, we identified barriers hindering patients' ability to accomplish the necessary tasks. Conclusions: Our findings highlight the substantial treatment burden faced by inner-city primary care patients self-managing CKD in combination with other chronic illnesses. Health care providers' awareness of treatment burden can inform the development of person-centered care plans that can help patients to better manage their chronic illnesses.